Prevalence of risk factors for non-communicable diseases among adult population residing in urban areas of Gangtok - Chettri, Meghna; Dhakal, Hemkala; Sharma, Pranita (International Journal Of Community Medicine And Public Health, 2026)
Background: Non-communicable diseases (NCDs) place a massive burden on global health and the economy, with cardiovascular diseases, cancer, and diabetes receiving the most focus. This study aimed to determine the prevalence of NCD risk factors among adults in urban Gangtok and identify associations between these risk factors and demographic variables. Methods: A descriptive survey design was utilized. A sample of 375 adults aged 29–59 residing in Ranipool was selected using probability sampling. Data was collected via interviews using the Community-Based Assessment Checklist (CBAC). Results: The point prevalence of NCD risk factors was 49.5%. Based on CBAC scores, 13.8% of respondents were at high risk (score > 4). Major risk factors included physical inactivity (71.2%) and clinical symptoms like shortness of breath (4%) and weight loss (2.9%). Risk factors were significantly associated with age, gender, religion, family income, and occupation (p < 0.05). Conclusions: These findings underscore the urgent need for lifestyle-based public health interventions in urban Gangtok to improve long-term health outcomes.